Self-heating effects in AlGaN/GaN HEMT heterostructures: Electrical and optical characterization - Naumov, A.V.; Kolomys, O.F.; Romanyuk, A.S.; Tsykaniuk, B.I.; Strelchuk, V.V.; Trius, M.P.; Avksentyev, A.Yu.; Belyaev, A.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The effect of self-heating on the transport characteristics and electronic properties of transistor AlGaN/GaN heterostructures was investigated. The electrical, micro-Raman and photoluminescence techniques were used for temperature estimations for transistor structures under electrical load. The thermal resistance of these structures has been calculated to obtain the temperature of conducting channel heating from the current-voltage characteristics. The differences in the obtained temperature data from applied techniques have been analyzed.